"Genderowe kilogramy". Płeć jako kategoria analityczna w badaniach postrzegania (nie)normatywności sylwetek osób o różnym indeksie masy ciała = "Gender kilograms": sex as an analytic category in research on the perception of (non)normativity of silhouettes of people with different body mass indices - Maj, Agnieszka; Kłonkowska, Anna M. (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to show in what way the notions of normativity of silhouette, its most desirable shape, proportion and mass, are determined by discourse connected with sex. The starting point of these considerations are the results of research within the sociology of the body. The research was carried out on a group of 60 individuals with the method of in-depth interview, whose theme concentrated on perception of normativity of silhouettes of people with different BMIs.
Keywords: obesity; slimness; sociology of body; stereotypes of sexes; otyłość; szczupłość; sociologia ciała; stereotypy płci